Caffeine and sports performance: the conflict between caffeine intake to enhance performance and avoiding caffeine to ensure sleep quality - Silva, H.; Del Coso, J.; Pickering, C. (Sports Medicine, 2025)
The ergogenic effects of caffeine have been reported in scientific literature over a wide spectrum of sporting activities. The current recommendation for caffeine supplementation is ingesting ~ 3-6 mg/kg about 1 h before the onset of exercise. However, some studies reporting caffeine-induced ergogenic effects during exercise have also reported increased activation and reduced sleep quality in the hours after caffeine ingestion. While most of the research on caffeine supplementation for sporting activities recommends the consumption of this stimulant to enhance performance, research focusing on athletes` sleep quality advises against this decision, especially before competition in the evening or later. Considering that some athletes often compete in the evening or later, the general recommendation of caffeine supplementation may be modified for these athletes as acute caffeine intake in these conditions may produce undesirable side effects such as insomnia and, potentially, reduced performance in subsequent days. In this review, we examine literature on this topic to help athletes and sports practitioners solve the dilemma between the convenience of using caffeine to enhance sports performance or avoiding caffeine to ensure sleep quality. This review identifies potential solutions for this decision, keeping the focus on athletes` well-being. Overall, the performance response to caffeine and the effect of this substance on sleep quality can vary interindividually and depend on the conditions of the exercise session (time of onset, duration, etc.). For this reason, nutritional practitioners should assess their athletes individually to resolve the conflict between caffeine ingestion and ensuring sleep quality on an individual basis, using simulated competitions with dual measurement of performance during exercise and unwanted effects in the following hours. In addition, the dose, timing, and source of caffeine supplementation can be individually adjusted to obtain performance benefits while reducing side effects for athletes ingesting caffeine before evening sporting events.